An anarchist criminology for uncertain times - Ferrell, Jeff (Journal of criminology, 2021)
Anarchist practices of direct action, decentralization, leaderless resistance, and mutual aid animate many forms of progressive activism that today percolate around the globe. For a new generation of activists, such practices are part of a more general anti-authoritarian reorientation to social life and social change. Here I suggest that this reorientation is worth exploring on its own terms, given that misunderstanding is all but assured if we try to make sense of it in the context of more conventional approaches. I argue in turn that street-level anarchist practices can productively reengage contemporary criminology with an increasingly uncertain world; attune criminology to the contested political dynamics of the present day; and help confront the precarious status of criminology and its practitioners.